Gene- and Disease-Based Expansion of the Knowledge on Inborn Errors of Immunity - Salnikova, Lyubov E.; Chernyshova, Ekaterina V.; Anastasevich, Lyudmila A.; Larin, Sergey S. (Frontiers in Immunology, 2019)
The recent report of the International Union of Immunological Societies (IUIS) has provided the categorized list of 354 inborn errors of immunity. We performed a systematic analysis of genes and diseases from the IUIS report with the use of the OMIM, ORPHANET and HPO resources. To measure phenotypic similarity we applied the Jaccard/Tanimoto (J/T) coefficient for HPO terms and top-level categories. Low J/T coefficients for HPO terms for OMIM or ORPHANET disease pairs associated with the same genes indicated high pleiotropy of these genes. Gene ORGANizer enrichment analysis demonstrated that gene sets related to HPO top-level categories were most often enriched in immune, lymphatic and corresponding body systems (for example, genes from the category ‘Cardiovascular’ were enriched in cardiovascular system). We presented available data on frequent and very frequent clinical signs and symptoms in inborn errors of immunity. With the use of DisGeNET, we generated the list of 25 IUIS/OMIM diseases with two or more relatively high score gene-disease associations, found for unrelated genes and/or for clusters of genes coding for interacting proteins. Our study showed the enrichment of gene sets related to several IUIS categories with neoplastic and autoimmune diseases from the GWAS Catalog and reported individual genes with phenotypic overlap between inborn errors of immunity and GWAS diseases/traits. We concluded that genetic background may play a role in phenotypic diversity of inborn errors of immunity.